2023
DOI: 10.14309/crj.0000000000001053
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Gastric Dieulafoy Lesions

Abstract: Dieulafoy lesions (DLs) are an uncommon nonvariceal cause of gastrointestinal bleeding. Although advanced endoscopic treatment is successful in majority, rarely radiologic intervention or surgery may be needed. Most of the reported case series described single DLs, and very limited data were available about multiple or synchronous DLs. We report a rare case of multiple DLs of the stomach refractory to repeated endoscopic interventions by hemoclips, regional diluted adrenaline injections, hemospray, and argon p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…While 90% of Dieulafoy's lesion cases are found in the proximal stomach, they may, albeit rarely, occur in other regions such as the duodenum, esophagus, and colorectal area [1,5]. The exact pathophysiology leading to the rupture and bleeding of these lesions remains uncertain, but one theory suggests a significant role of arterial thrombosis and subsequent necrosis [4,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While 90% of Dieulafoy's lesion cases are found in the proximal stomach, they may, albeit rarely, occur in other regions such as the duodenum, esophagus, and colorectal area [1,5]. The exact pathophysiology leading to the rupture and bleeding of these lesions remains uncertain, but one theory suggests a significant role of arterial thrombosis and subsequent necrosis [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Dieulafoy's lesion (DL), also referred to as a cirsoid aneurysm or submucosal arterial malformation, is a rare yet severe etiology of acute gastrointestinal (GI) bleeding. This condition presents a significant clinical challenge due to its association with high morbidity and mortality rates [1]. The condition was first identified by Gallard in 1884, adding to our understanding of uncommon causes of GI bleeding [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pemmada et al recognized that patient education is important to prevent pill esophagitis in developing countries, particularly in relation to the usage of over-the-counter medicines. 2 A pilot study by Bharadwaj et al showed that the use of rotational thromboelastometry reduced fresh frozen plasma requirement in patients without liver disease with deranged screening coagulation test, undergoing therapeutic endoscopic procedures without any increased risk of early/late rebleeding, and 30-day mortality. 3 The study by Rana et al revealed that patients with walled-off necrosis and disconnected pancreatic duct, treated with lumen apposing metal stent and direct endoscopic necrosectomy had lower risk of pain recurrence or pancreatic fluid collections.…”
mentioning
confidence: 99%